1989
DOI: 10.1530/jrf.0.0870603
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of oestradiol and of the uterus in the maintenance of the corpus luteum in the pseudopregnant brown hare (Lepus europaeus)

Abstract: by the large ovarian follicles is the main luteotrophic factor in the brown hare. In old hares, the large amount of interstitial tissue could secrete oestrogens, and thus maintain pseudopregnancy. On Day 7 of pseudopregnancy, the uterus secretes a luteotrophic substance acting either directly on the ovary, or via the pituitary, to maintain oestradiol secretion by the follicles. In long-term hysterectomized females, the CL would be able to develop independently of any trophic substance, but for a reduced durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Adams et al (1981) demonstrated that the phytoestrogenic syndrome in sheep involves extension of the life of the corpus luteum in a proportion of ewes and therefore prolongation of the influence of progesterone and resultant pathologic changes. In the rabbit, exogenous estrogens do not prolong the life of the corpus luteum (Miller and Keynes, 1976), whereas they do in hares (Caillol et al, 1989). Hence, the presence of lesions in hares exposed to phytoestrogens but not in sympatric rabbits is consistent with our observations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Adams et al (1981) demonstrated that the phytoestrogenic syndrome in sheep involves extension of the life of the corpus luteum in a proportion of ewes and therefore prolongation of the influence of progesterone and resultant pathologic changes. In the rabbit, exogenous estrogens do not prolong the life of the corpus luteum (Miller and Keynes, 1976), whereas they do in hares (Caillol et al, 1989). Hence, the presence of lesions in hares exposed to phytoestrogens but not in sympatric rabbits is consistent with our observations.…”
Section: Discussionsupporting
confidence: 90%
“…Cystic endometrial hyperplasia is the major indication of phytoestrogenism in sheep (Bennetts et al, 1946). Hares are particularly sensitive to the luteotrophic effect of exogenous estrogen, which can double the length of pseudopregnancy in that species (Caillol et al, 1986(Caillol et al, , 1989. The formation of secretory cells in the oviducts can be induced by exogenous estrogen (Fredricsson, 1959cited by Odor et al, 1989.…”
Section: Discussionmentioning
confidence: 99%
“…The uterine enlargement (Calliol et al, 1989a), increased progesterone (Calliol and Martinet, 1976;Calliol etal., 1991) and estradiol (Caillol et al, 1989a(Caillol et al, , 1991Semizorova et al, 1990) levels in the blood of females have been reported. In males, growth of testicles and increased blood testosterone levels (Calliol et al, 1989b) during the reproductive cycle have been described.…”
Section: Introductionmentioning
confidence: 94%
“…Enlargement of the uterus (Calliol et al, 1989a) and increases in the levels of progesterone (Calliol and Martinet, 1976;Calliol etal., 1991) and oestradiol (Caillol et al, 1989a(Caillol et al, ,b, 1991Semizorova et al, 1990) have been documented. These authors studied mostly cage-bred brown hares, not animals from the wild.…”
Section: Introductionmentioning
confidence: 96%